Targeted Prodrug Approaches for Hormone Refractory Prostate Cancer. Issue 3 (22nd December 2014) - Aloysius, Herve; Hu, Longqin
Abstract Due to the propensity of relapse and resistance with prolonged androgen deprivation therapy (ADT), there is a growing interest in developing non‐hormonal therapeutic approaches as alternative treatment modalities for hormone refractory prostate cancer (HRPC). Although the standard treatment for HRPC consists of a combination of ADT with taxanes and anthracyclines, the clinical use of chemotherapeutics is limited by systemic toxicity stemming from nondiscriminatory drug exposure to normal tissues. In order to improve the tumor selectivity of chemotherapeutics, various targeted prodrug approaches have been explored. Antibody‐directed enzyme prodrug therapy (ADEPT) and gene‐directed enzyme prodrug therapy (GDEPT) strategies leverage tumor‐specific antigens and transcription factors for the specific delivery of cytotoxic anticancer agents using various prodrug‐activating enzymes. In prostate cancer, overexpression of tumor‐specific proteases such as prostate‐specific antigen (PSA) and prostate‐specific membrane antigen (PSMA) is being exploited for selective activation of anticancer prodrugs designed to be activated through proteolysis by these prostate cancer‐specific enzymes. PSMA‐ and PSA‐activated prodrugs typically comprise an engineered high‐specificity protease peptide substrate coupled to a potent cytotoxic agent via a linker for rapid release of cytotoxic species in the vicinity of prostate cancer cells following proteolytic cleavage. Over the past two decades, various such prodrugs have been developed and they were effective at inhibiting prostate tumor growth in rodent models; several of these prodrug approaches have been advanced to clinical trials and may be developed into effective therapies for HRPC.